1998
DOI: 10.1007/s004649900587
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized comparison of laparoscopic ultrasonography using a flexible-tip ultrasound probe and intraoperative dynamic cholangiography during laparoscopic cholecystectomy

Abstract: LIOU performed by experienced surgeons is a good and effective method to assess the CBD, including the neighboring structures of hepatoduodenal ligament. Using powerful, flexible-tip ultrasound probes, CBD exploration can be done in a longitudinal fashion, which is necessary for good anatomical clarity. A lack of adverse effects, shorter examination times, and lower costs are some of the advantages of this method. The most important advantage is the possibility of unlimited repetition, especially if there is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 24 publications
2
37
0
2
Order By: Relevance
“…12,13,15,17,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] There were 4,566 patients in the IOC group and 5,044 in the LUS group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13,15,17,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] There were 4,566 patients in the IOC group and 5,044 in the LUS group.…”
Section: Resultsmentioning
confidence: 99%
“…12,31,33,34,39 These studies looked at the visualisation of the intrahepatic ducts, common hepatic duct, extrapancreatic CBD and intrapancreatic CBD. IOC appeared to be better at detecting the intrapancreatic CBD (random effects, RR: 1.15, 95% CI: 1.04-1.26, p=0.007) but there was no significant difference in identifying the extrapancreatic CBD (random effects, RR: 1.04, 95% CI: 0.95-1.12, p=0.60).…”
Section: Anatomical Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it does not require new X-ray apparatus, radiologists, or laboratory technicians. Many studies, including two randomized control trials, have reported that visualization of the biliary tract anatomy and diagnostic performance of IOUS for bile duct stones are as high, or better, than those for cholangiography [17,[21][22][23] . It has also been reported that IOUS decreases the necessity to perform cholangiography [29,30] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, IOUS requires a shorter examination time [17][18][19] , is safe without incurring radiation exposure, www.wjgnet.com and is minimally invasive [18,20] . It has been reported that IOUS allows for visualization equal to or better than that of cholangiography [17,[20][21][22][23] in the case of biliary anatomy and diagnosis of bile duct stones. However, there have been few studies that have investigated whether the routine implementation of IOUS decreases BDI during LC [24] .…”
Section: Introductionmentioning
confidence: 99%